Performance Analysis of FRP Reinforced Concrete After Corrosion Damage - Mansur, Achmad Zultan (invotek, 2025)
Corrosion in bridge girder beams frequently leads to significant structural damage, such as concrete spalling and reduced reinforcement, which directly impacts the bending capacity. This study experimentally assessed the efficacy of a combined repair strategy of grouting and Glass Fiber Reinforced Polymer (GFRP) reinforcement on simulated damaged reinforced concrete beams. Twelve beams were tested with various repair configurations, including a standalone grouting repair and a combination of grouting with GFRP in strip and U-wrap configurations. The primary objective was to comprehensively evaluate the enhanced flexural capacity and failure modes of these repaired beams. The results indicated that GFRP reinforcement, particularly the U-wrap configuration, significantly improved the beams' flexural capacity. Beams with the GFRP U-wrap configuration achieved an average maximum load of 32.50 kN, surpassing the control beam's 29.74 kN by 9.27%. Conversely, a standalone grouting repair drastically decreased the load capacity to 14.49 kN, highlighting its inefficiency in strength restoration. Debonding failure at the grout-concrete interface was identified as the primary cause of this reduction. The U-wrap configuration outperformed the strip configuration, likely due to its enhanced shear resistance and confinement. The GFRP strain analysis showed linear behavior at low loads but significant deviations at higher loads, which indicates debonding. All beams exhibited a dominant flexural cracking failure mode, with the addition of GFRP reducing the number of cracks. In conclusion, the combined grouting and GFRP reinforcement, especially the U-wrap configuration, proved to be an effective strategy for repairing damaged RC beams. However, achieving strong adhesion between the repair materials and the concrete is crucial to prevent debonding and optimize structural performance. Further research on enhancing adhesion and optimizing GFRP configurations is recommended.